Efficacy of fluralaner flavored chews (Bravecto®) administered to dogs against the adult cat flea, Ctenocephalides felis felis and egg production - Michael W Dryden; Vicki Smith; Tashina Bennett; Lisa Math; James Kallman; Kathleen Heaney; Fangshi Sun (Parasites & Vectors, 2015)
Abstract Background Fluralaner is a potent insecticide and acaricide with rapid and persistent efficacy. This study measured the efficacy of fluralaner flavored chews (Bravecto®, Merck Animal Health) administered to dogs against adult Ctenocephalides felis felis and egg production. Methods Twelve purpose-bred dogs were randomly allocated to two groups of six dogs each. Dogs in treatment group 1 were administered a single fluralaner flavored chew to achieve a minimum dose of at least 25 mg/kg while treatment group 2 served as untreated controls. On Days −2, 28, 56, 84, 91, 98, 105, 112, and 120 post-treatment, each dog was infested with approximately 200 unfed cat fleas, C. felis felis (KS1 strain). Forty-eight hours after treatment and 48 h after each infestation, eggs were collected over a 3-h period, counted and viability determined. Dogs were combed to remove any remaining fleas. Results Treatment of dogs with oral fluralaner provided a 100 % reduction in flea counts 48 h after treatment and within 48 h of every post-treatment infestation through Day122. Egg production from fluralaner treated dogs was reduced by 99.9 % (two eggs from one dog) within 48 h after treatment and not a single egg (100 % efficacy) was thereafter collected from treated dogs. Adult flea counts and egg production from the fluralaner-treated dogs were significantly lower than for non-treated controls at all post-treatment evaluations (P < 0.001). The two eggs collected from the single treated dog 48 h after treatment did not produce any adult fleas. As no additional eggs were collected from treated dogs, no viability assessment was performed. Conclusions A single oral dose of fluralaner flavored chews provided 100 % efficacy against repeated flea infestations on dogs for 4 months. Fluralaner reduced egg production of activity reproducing female fleas by 99.9 % and then killed every single female flea before any eggs could be produced following each subsequent re-infestation for the entire 122-day evaluation period.